Prevalence of Vibrio cholerae in Coastal Alternative Supplies of Drinking Water and Association with Bacillus-Like Spore Formers - Shishir, Md. Asaduzzaman; Mamun, Md. Al; Mian, Md. Mahmuduzzaman; Ferdous, Umme Tamanna; Akter, Noor Jahan; Suravi, Rajia Sultana; Datta, Suvamoy; Kabir, Md. Ehsanul (Frontiers in Public Health, 2018)
The scarcity of hygienic drinking water is a normal phenomenon in the coastal areas of Bangladesh due to the high salinity of ground water. The inhabitants of this locality, therefore, live on alternative supplies of water including rain-fed pond water, and rainwater with persistent complex microbial interactions therein, often contaminated with life-threatening pathogens. Hence, this study was aimed at analyzing the prevalence of Vibrio cholerae (Vc) in the alternative drinking waters of Mathbaria, a coastal subdistrict neighboring the Bay of Bengal, the efficacy of pond sand filter (PSF) and the co-association among Bacillus-like spore formers (Sf) and Vc. Vc presumably entrapped into the membrane filter was enriched in alkaline peptone water medium and was isolated on selective thiosulfate-citrate-bile salts-sucrose and taurocholate-tellurite-gelatin agar media. They were finally identified by immunochromatographic one step rapid test and serology test. A total of 26% Vc positive samples were obtained out of 100 [ponds—48, household (HH)—29, and PSFs—23] where 13% cases were pathogenic (Vc O1) and 13% were non-pathogenic (Vc non-O1/non-O139). The distribution of Vc as observed was 33, 26, and 13.8% in waters derived from pond surface, PSF, and HH reservoirs, respectively, and for pathogenic type, it was 62.5%, 50%, and nil, respectively. Although none of the samples was identified with pathogenic Vc O139, the statistics represents a significant and augmentative risk of cholera outbreak in the focused area. The antibiotic sensitivity pattern in this study resembled the trend observed during last few years for Vc. The PSF demonstrated its inability to remove Vc from any of the samples and in addition, the filter itself was evidenced to be the source of pathogens and spores in further contamination and transmission. The development of biofilm in the PSF could be hypothesized as the reservoir in contaminating pathogen-free water samples. From the test of homogeneity, the risk levels of alternative water sources were estimated equal regarding Vc. Simultaneously, it was determined statistically that the prevalence of Vc, by no means, is influenced by Bacillus-like Sf be it for pond surface, HH, or PSF derived water.